Improvement of Mathematics Learning Outcomes by Applying The Missouri Mathematics Project Learning Model And Dienes Game Theory - Muhammad Fakhri; Marhan Taufik; Agung Deddiliawan Ismail (Department of Mathematics Education University of Muhammadiyah Malang, 2020)
Based on the results of first observations and interviews with class teachers at SMP Negeri 06 Batu, mathematics learning outcomes for class VIIA students in the End Semester Test (EST) even semester of the 2018/2019 school year had an average grade below the Minimum Criteria of Mastery Learning (MCML) and only about 5 students reached MCML. This research aims to improve the mathematics learning outcomes of Grade VIII A students by applied the Missouri Mathematics Project (MMP) learning model combined with Dienes Game Theory. This research method used the Classroom Action Research (CAR) method with application for 4 meetings in 2 cycles. Each cycle there are 4 stages: planning, implementing, observing, and reflecting. Data collection techniques used tests, interviews, observations, and document studies. Data collection techniques used were tests, interviews, observations, and document studies. The results showed that by applying the MMP learning model combined with Dienes Games Theory, it could improve mathematics learning outcomes for students of class VIII A. The results of EST grade VII A students as the initial reference were 73,8, to 84.8 in cycle 1, and 86 .0 in cycle 2.